Ciliates (Alveolata, Ciliophora) as bioindicators of environmental pressure: A karstic river case - Antonija Kulaš (Elsevier, 2021)
Ciliates are single celled eukaryotes recognized as key players in the microbial loop of aquatic ecosystems. The present study was carried out on the Krka River (Croatia), a karst freshwater ecosystem characterized by tufa barriers, biomineralization and highly diverse aquatic communities. The main aims of the study were to investigate ciliate community structure in the biofilm (i.e. periphyton) samples collected from light- and dark-exposed lithified tufa/stones. Furthermore, by establishing links between ciliate community patterns and environmental parameters, we aimed to assess the bioindicator potential of specific ciliate taxa for environmental monitoring of freshwater habitats. The periphyton sampling was performed at four representative sites of the river source, upstream, middle and downstream river sections. Ciliate community was investigated via traditional microscopy analyses and environmental DNA (eDNA) metabarcoding (Illumina sequencing of the hypervariable V9-region of the SSU rRNA gene). The molecular approach recorded a substantially higher number of ciliate taxa, most of which taxonomically belonging to genera typically occurring in tufa barriers. The results from microscopy analyses did not show any links between ciliate community structure and sampling location. However, eDNA approach indicated significant differences among the sampling locations regarding the ciliate community structure. Thereby, hydrological parameters and saprobiological classification of the sampling sites were the main structuring factors for ciliate community. The coupling of eDNA metabarcoding with the morphological approach provides a robust, in-depth analytical system in elucidating the bioindicator potential of ciliated protists.